2021
DOI: 10.3390/ijerph18020479
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitudes, and Practices toward Seasonal Influenza Vaccine in Saudi Arabia: A Cross-Sectional Study

Abstract: Objectives: Increasing national influenza vaccination rates continues to be a challenge for Saudi Arabia. Therefore, the purpose of this study was to explore the Saudi public perceptions toward seasonal influenza vaccination and their association with the rate of vaccination. Methods: Individuals aged 15 years and older were surveyed about their knowledge, attitudes, and practices toward the seasonal influenza vaccine using a previously developed and validated 19-item online questionnaire. The impact of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
7
25
2
Order By: Relevance
“…We found an association between the higher education of the respondents and the possibility for administration of an influenza vaccine (2=27.002, p=0.00002), which correlates with studies of other authors 26 . It might seem intuitive that higher education predisposes to a higher vaccination rate, but in the literature this theory is inconsistent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found an association between the higher education of the respondents and the possibility for administration of an influenza vaccine (2=27.002, p=0.00002), which correlates with studies of other authors 26 . It might seem intuitive that higher education predisposes to a higher vaccination rate, but in the literature this theory is inconsistent.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, an Australian study found that in the general population the two most stated reasons for not accepting the vaccine were "situation is not serious enough" and "I am not at risk" 32 . The positive view toward the influenza vaccine safety and efficacy has been identified as strongly associated with higher rates of vaccine uptake 26 . The European Centre for Disease Prevention and Control studied the so-called "vaccine hesitancy" phenomenon and determined that the major determinants for opposition to vaccination were concerns about vaccine safety and mistrust of the pharmaceutical industry [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Such a finding was in accordance with Alqahtani et al (2017), who reported that HCWs were the main source of information [ 11 ]. However, other studies ranked mass media as the first and HCWs as the third source of vaccine information for the general Saudi population [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female and lower age groups were found to have lower levels of knowledge of influenza and influenza vaccines [ 16 ]. Another cross-sectional study involved 790 Saudi citizens from the general population and showed that the participants who believed the influenza vaccine to be safe, efficacious, given at a specific time of the year and were aware of the need to be vaccinated were more likely to have received the vaccine [ 17 ]. A study by Alabbad et al (2018), which enrolled three groups (adult patients, parents, and HCWs) of 300 Saudis, showed that the most common reasons for vaccination were awareness campaigns and being medical staff (36%).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary literature reported that the gap or lack of knowledge of chronic diseases can increase morbidity and mortality ( 12 ). However, a number of studies evaluated the knowledge, attitudes, and practice on previous pandemics, such as malaria ( 13 ), intestinal parasitic infection ( 14 ), and influenza ( 15 , 16 ). Until now, there are still limited studies that evaluated behavioral changes toward COVID-19 from a community perspective.…”
Section: Introductionmentioning
confidence: 99%